Impact of obstructive sleep apnea on the expression of inflammatory mediators in diabetic macular edema. Issue 1 (January 2023) - Yang, Yelin; Somani, Sohel
Purpose: To determine differences in inflammatory markers expressed in diabetic macular edema (DME) patients with and without obstructive sleep apnea (OSA). Methods: This was a prospective, cross-sectional study. Patients with treatment naive DME were enrolled in the study. They were stratified into 2 groups based on Apnea Hypopnea Index (AHI) from overnight polysomnography: OSA + (AHI ≥ 15) and OSA – (AHI<15). Multiplex immunoassay was performed for aqueous and serum cytokines including VEGF, placental growth factor (PGF), ICAM, IL2, IL3, IL6, IL8, IL10, IL17, vascular cell adhesion molecule-1 (VCAM1), monocyte attractant protein-1 (MCP1), epidermal growth factor (EGF) and platelet derived growth factor (PDGF). Statistical significance was defined as p < 0.004 using Bonferroni correction. Results: 32 DME positive patients were enrolled in the study; of which 17 patients were OSA + and 15 OSA-. The OSA + cohort had significantly higher levels of serum EGF (p = 0.003), and trended towards higher levels of most serum cytokines including ICAM and IL6. OSA- cohort had significantly higher levels of aqueous IL17 compared to the OSA + cohort (2.97 ± 1.7 vs. 1.4 ± 0.46 pg/mL, p = 0.004). There were no significant differences in other aqueous cytokines. Conclusions: OSA + group trended towards higher levels of most serum inflammatory markers, suggesting a greater pro-inflammatory state. However, they did not have significantly greater level of aqueous cytokines.